The use of the Curriculum into Plays to School Belonging among primary school students (Journal of the College of Basic Education, 2023)
The basic education stage, especially in the basic education stage, is effective in improving education and teamwork, developing skills and physical performance, and transforming the student from a mere recipient into an effective tool in the educational stage, the teacher. On the other hand, this is one of the problems that the participants in the institute suffer from, and some of them are in reading and writing. Or isolation from the environment that he feels that he does not belong to, which leads to his punishment by others in the first case, or a decrease in his motivation to study and his academic level drops, so it has become realistic for educators to find something that restores his confidence in his surrounding environment, represented by the school and what is in it and who is in it, Therefore, he must be involved in extra-curricular activities, sports, art, or scouting, or activities that are presented in the classroom and contain scientific lessons in their content, in order to involve him in the group and bring him back to its ranks and his sense of belonging to it again.